Archaeological Discoveries from Tenea - Korka, Eleni; Lefantzis, Michalis; Corso, Antonio (Actual Problems of Theory and History of Art, 2019)
This article focuses on the identification and excavation of important artworks of the ancient city of Tenea, south of Corinth, where the modern villages Chiliomodi and Clenia are located. In the past, three kouroi were found in the broader area, one is now in Munich, and the other two are in the Archaeological Museum of Corinth. In the excavation a large section of the necropolis has been found. In particular an archaic sarcophagus bearing the painting of two lions in heraldic position is particularly impressive, a large mausoleum also found on the site is noteworthy. A relief slab with Hermes, a now lost fragment of another slab with Dionysos and finally a relief panel also lost but copied in a drawing by Stuart in the late 18th century may have been pertinent to a sekos which may have existed in the city in celebration of the victory of Octavianat Actium dating in the middle Augustan times.
Keywords: Tenea; Corinth; Troy; Strabo; Pausanias; lions; Hermes; Dionysos; Augustus